Water for Food and Energy Security : An Assessment of the Impacts of Water Scarcity on Agricultural Production and Electricity Generation in the Middle East and North Africa - Miralles-Wilhelm, Fernando; Hejazi, Mohamad; Kim, Song; Yonkofski, Catherine; Watson, David; Kyle, Page; Liu, Yaling; Vernon, Chris; Delgado, Alison; Edmonds, Jae; Clarke, Leon (World Bank, Washington, DC, 2018)
Water, energy, and agriculture have been conventionally dealt with separately in investment planning. For each of these sectors, regulatory frameworks, organizations, and infrastructures have been put in place to address sector-specific challenges and demands. As the Middle East and North Africa works towards building a more sustainable future, a nexus approach that considers the risks and synergies among these sectors is needed. To demonstrate the added value of a nexus approach, this report applies scenario analysis and integrated assessment modelling of the water-energy-food nexus to the Middle East and North Africa. The analysis finds that water scarcity increases in all countries in the region over the coming decades, mostly due to growing demands. More importantly, the analysis finds that many countries in the region could run out of fossil groundwater by 2050 unless measures to curb unsustainable abstraction are implemented. The impacts of growing scarcity on agriculture are significant, with production projected to drop by 60 percent by 2050 in some countries. On the upside, reducing the dependence of the agricultural and energy sectors on water and transitioning to renewable energies can reduce water scarcity, at the same time reducing greenhouse gas emissions.